“A Statistical Study of Attentiveness of Cryptocurrency among the Student’’ (International Journal of Food and Nutritional Sciences, 2023)
In this technological and digitization era, we can buy all kind of goods and services with digital money. Considering this the emerging era is of cryptocurrency which is a digital, encrypted and decentralized currency which is not regulated, managed and maintained by any central authority. However, if the technology enhances simultaneously frauds will increase. In regards this study aimed to assess the awareness of cryptocurrency among the students of Bilaspur. Also aim to introduce emerging era of cryptocurrency for upcoming generation, to determine the willingness of people to choose Cryptocurrencies an investment tool. The results show there insignificantly less people are aware about the various aspects and dimensions of cryptocurrency. Whereas due to lack of awareness about cryptocurrency only 52% students interested to invest in the cryptocurrency or willing to choose cryptocurrency as an investment tool.